Chromosome‐level genome assembly of the razor clam Sinonovacula constricta (Lamarck, 1818). (28th October 2019) - Ran, Zhaoshou; Li, Zhenzhen; Yan, Xiaojun; Liao, Kai; Kong, Fei; Zhang, Lin; Cao, Jiayi; Zhou, Chengxu; Zhu, Peng; He, Shan; Huang, Wanlong; Xu, Jilin
Abstract: Bivalves, a highly diverse and the most evolutionarily successful class of invertebrates native to aquatic habitats, provide valuable molecular resources for understanding the evolutionary adaptation and aquatic ecology. Here, we reported a high‐quality chromosome‐level genome assembly of the razor clam Sinonovacula constricta using Pacific Bioscience single‐molecule real‐time sequencing, Illumina paired‐end sequencing, 10X Genomics linked‐reads and Hi‐C reads. The genome size was 1, 220.85 Mb, containing scaffold N50 of 65.93 Mb and contig N50 of 976.94 Kb. A total of 899 complete (91.92%) and seven partial (0.72%) matches of the 978 metazoa Benchmarking Universal Single‐Copy Orthologs were determined in this genome assembly. And Hi‐C scaffolding of the genome resulted in 19 pseudochromosomes. A total of 28, 594 protein‐coding genes were predicted in the S. constricta genome, of which 25, 413 genes (88.88%) were functionally annotated. In addition, 39.79% of the assembled genome was composed of repetitive sequences, and 4, 372 noncoding RNAs were identified. The enrichment analyses of the significantly expanded and contracted genes suggested an evolutionary adaptation of S. constricta to highly stressful living environments. In summary, the genomic resources generated in this work not only provide a valuable reference genome for investigating the molecular mechanisms of S. constricta biological functions and evolutionary adaptation, but also facilitate its genetic improvement and disease treatment. Meanwhile, the obtained genome greatly improves our understanding of the genetics of molluscs and their comparative evolution.